Chemical Analysis of Lipid and Extracts from Microalgae - Nurul Nadya Binti Shahabudin, Nurul Nadya (Universiti Teknologi Petronas, 2011)
Microalgae are able to survive in highly competitive environment synthesized by diverse compounds from different metabolic pathways. Microalgae known as “cell factories” due to the potential for producing biochemical elements such as lipid, protein, carbohydrates, amino acids and free fatty acids derived from their primary and secondary metabolite. These elements may have potential economic impact in bio-energy, environmental remediation, food science, pharmaceutical industry and public health. The studies undertaken in this project are based on green microalgae species. The cell growth profile at condition (temperature: ~250C, pH: ~7.5, and light intensity) was established. The specific growth rate and doubling time for Nannochloropsis spp. (0.30 million cell/ day; 2.33 days), Tetraselmis batan spp. (0.20 million cell/ day; 3.47 days), Isochrysis galbana spp. (0.18 million cell/ day; 3.88 days) and Pavlouva lutheri spp. (0.15 million cell/ day; 4.56 days) were calculated. Lipid, biodiesel and glycerol and pigments for Nannochloropsis spp. were 17.80%, 8.00% and 3.80% respectively. By using spectrophotometer, chlorophyll a (0.335 mg/ g), chlorophyll b (0.614 mg/g) and total carotenoid (0.108 mg/g) were calculated. pH 8.0 is the optimum pH level for green microalgae growth and thus, produce the maximum percentage of lipid content.